Lightweight high-strength bulletproof carbon block and preparation method thereof
By using fine-grained carbon powder for press forming and pressurized sintering, the shortcomings of carbon block materials in terms of strength, hardness and toughness are solved, and the preparation of high-performance, lightweight bulletproof carbon blocks is realized.
Patent Information
- Application Number
- CN202510077139.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-15
AI Technical Summary
The existing carbon block materials have shortcomings in strength, hardness and toughness, which are difficult to meet the high performance needs of lightweight bulletproof materials.
The carbon powder with D50 of 0.1~5μm was pressed and sintered under a sintering pressure of 1~5MPa, and the heating rate was controlled to be 0.1~0.3℃/min to form a high density carbon block.
It has achieved a lightweight, high-strength bulletproof carbon block with high yield, with excellent mechanical properties and impact resistance, and can absorb large impact energy per unit mass.
Smart Images

Figure CN119822832A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon materials, and specifically relates to a lightweight and high-strength bulletproof carbon block and a preparation method thereof. Background Art
[0002] With the rapid development of various military technologies, new highly lethal weapons are constantly being developed and applied, which has promoted the rapid development of anti-armor weapon technology. The battlefield survivability of weapons and equipment has put forward higher requirements on the performance of armor protection materials, which has promoted the further development of bulletproof materials.
[0003] Traditional metal bulletproof materials (steel, aluminum) are difficult to meet the lightweight and efficient combat requirements of modern warfare. The development of high-strength, high-hardness, high-toughness, low-density protective materials is an effective way to enhance the combat capability of individual soldiers. Continuously improving its lightweight protective capabilities is the eternal theme of the development of individual equipment. At present, lightweight bulletproof materials are mainly based on alumina, silicon carbide, and boron carbide ceramics, with a density between 2.5 and 4.0 g / cm 3 The industrialized bulletproof composite ceramics are mainly silicon carbide / boron carbide composite ceramics.
[0004] Carbon graphite materials, mainly carbon blocks and graphite blocks, have the typical characteristics of low density and high strength. Compared with graphite blocks, carbon blocks have lower density (<1.8 g / cm 3 ), higher strength, hardness and toughness, making it a model of lightweight and high-strength bulk materials. However, due to the intrinsic defects of carbon (pores, intrinsic strength), its strength, hardness and toughness are lower than those of modern lightweight ceramics.
[0005] Therefore, on the premise of achieving a high yield of carbon blocks, how to further improve their strength, hardness and toughness and meet the requirements of lightweight (density <2.0 g / cm³) has become a core challenge faced by the research and development of the next generation of high-efficiency new bulletproof materials. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a lightweight and high-strength bulletproof carbon block and a preparation method thereof. The present invention has a high yield rate, and the prepared carbon block has a low open porosity, and has excellent mechanical properties and impact resistance, and can absorb a large impact energy per unit mass.
[0007] The technical solution of the present invention is achieved in this way: A method for preparing a lightweight and high-strength bullet-proof carbon block comprises: pressing carbon powder with a D50 of 0.1-5 μm to obtain a green body, and then placing the green body in a pressure sintering furnace and calcining at 1-5 MPa to obtain the lightweight and high-strength bullet-proof carbon block.
[0008] Furthermore, the carbon powder is one or more of granulated powder, raw asphalt coke, raw petroleum coke and mesophase carbon microspheres.
[0009] Furthermore, the specific steps of compression molding are: first, pre-molding is performed on a flat vulcanizer at a pressure of 1-15 MPa for 10-30 s, and then the green body is obtained by holding the pressure at 150-250 MPa for 10-20 min on a cooling press, and then the green body is left for more than 12 hours.
[0010] Furthermore, during calcination, the temperature is raised to 800-1200°C at a heating rate of 0.1-0.3°C / min under the protection of an inert gas, maintained at that temperature for 2-6 hours, and then cooled to room temperature.
[0011] Furthermore, the heating rate is 0.2°C / min.
[0012] Furthermore, during sintering, the pressure in the pressure sintering furnace is 3 MPa.
[0013] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses carbon powder with a D50 of 0.1-5 μm as raw material, and after compression molding, it is sintered into a carbon block at a heating rate of 0.1-0.3°C / min under a sintering pressure of 1-5 MPa. Low-particle carbon powder can reduce porosity and increase the bonding strength of the carbonaceous interface, thereby obtaining a denser block, but it also increases the risk of cracking. The present invention combines a suitable heating rate and sintering pressure to avoid cracking of the sintered carbon block, effectively improving the yield rate.
[0014] At the same time, pressure sintering can further improve the density and mechanical properties of the carbon block without changing the properties of the raw materials, thereby improving the strength and toughness of the carbon block.
[0015] 2. The yield rate of the carbon block prepared by one-time calcination of the present invention reaches 100%, and the volume density of the carbon block prepared by one-time calcination can reach 1.74 g / cm 3 , open porosity 1.2%, flexural strength 152.35 MPa, compressive strength 501.72 MPa; and has excellent impact resistance. On average, each gram of carbon block can withstand a maximum impact force of 413.37 N and absorb 409.47 mJ of impact energy.
[0016] 3. The preparation process of the present invention is simple to operate and can prepare a lightweight and high-strength bullet-proof carbon block by one calcination, providing new insights into the preparation of the next generation of efficient and lightweight new bullet-proof materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 -Optical photographs of the carbon blocks prepared in Comparative Examples 2 and 3.
[0018] Figure 2 -Comparison of mechanical properties of carbon blocks prepared in Example 1, Comparative Example 1, and Comparative Examples 4 to 7.
[0019] Figure 3 -Comparison results of nanoindentation load-displacement curves (ac) and hardness (d), Young's modulus (e) and indentation depth (f) of the carbon blocks prepared in Example 1 and Comparative Example 1 and Comparative Examples 4 to 7.
[0020] Figure 4 -SEM images of the carbon blocks prepared in Example 1 and Comparative Example 1 and Comparative Examples 4 to 7.
[0021] Figure 5 -Comparison of the impact resistance of the carbon blocks prepared in Example 1, Comparative Example 1, and Comparative Examples 4 to 7.
[0022] Figure 6 - Fragment reconstruction diagram of the carbon blocks prepared in Comparative Example 7 and Example 1 after the impact test. DETAILED DESCRIPTION
[0023] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0024] Example 1 A method for preparing a lightweight and high-strength bulletproof carbon block comprises the following steps: (1) Green petroleum coke with an average particle size of 2 μm was molded on a flat vulcanizer at a pressure of 3 MPa. The block was then kept at an isostatic pressure of 200 MPa for 10 min and left for more than 12 h to obtain a green body.
[0025] (2) The green block obtained in (1) was placed in a pressure sintering furnace. Under 3 MPa argon protection, the temperature was raised to 1050 °C at a rate of 0.2 °C / min and kept at that temperature for 4 h, then the temperature was lowered to below 200 °C at a rate of 0.1 °C / min, and then naturally cooled to room temperature, thereby obtaining the lightweight and high-strength carbon block, which was named SCB-M2.
[0026] Comparative Example 1 A method for preparing a self-sintered carbon block comprises the following steps: (1) Green petroleum coke with an average particle size of 2 μm was molded on a flat vulcanizer at a pressure of 3 MPa. The block was then kept at an isostatic pressure of 200 MPa for 10 min and left for more than 12 h to obtain a green body.
[0027] (2) The green blocks obtained in (1) are placed in a traditional box-type five-sided furnace sagger, and the remaining space is filled with buried sintering materials. The sintering pressure is close to normal pressure, i.e. 0.1 MPa.
[0028] (3) The sagger prepared in step (2) was placed in a five-sided furnace. Under argon protection, the temperature was raised to 1050 °C at a rate of 0.2 °C / min and kept at that temperature for 4 h. The temperature was then lowered to below 200 °C at a rate of 0.1 °C / min and then naturally cooled to room temperature to obtain the self-sintered carbon block, which was named SCB-K2.
[0029] Comparative Example 2 A method for preparing a self-sintered carbon block comprises the following steps: (1) Green petroleum coke with an average particle size of 2 μm was molded on a flat vulcanizer at a pressure of 3 MPa. The block was then kept at an isostatic pressure of 200 MPa for 10 min and left for more than 12 h to obtain a green body.
[0030] (2) The green block obtained in (1) was placed in a pressure sintering furnace. Under 3 MPa argon protection, the temperature was raised to 1050 °C at a rate of 0.4 °C / min and kept at that temperature for 4 h, then the temperature was lowered to below 200 °C at a rate of 0.1 °C / min, and then naturally cooled to room temperature, thereby obtaining the lightweight and high-strength carbon block, which was named SCB-M2-0.4T.
[0031] Comparative Example 3 A method for preparing a lightweight and high-strength bulletproof carbon block comprises the following steps: (1) Green petroleum coke with an average particle size of 2 μm was molded on a flat vulcanizer at a pressure of 3 MPa. The block was then kept at an isostatic pressure of 200 MPa for 10 min and left for more than 12 h to obtain a green body.
[0032] (2) The green block obtained in (1) was placed in a pressure sintering furnace. Under 6 MPa argon protection, the temperature was raised to 1050 °C at a rate of 0.2 °C / min and kept at that temperature for 4 h, then the temperature was lowered to below 200 °C at a rate of 0.1 °C / min, and then naturally cooled to room temperature, thereby obtaining the lightweight and high-strength carbon block, which was named SCB-M2-2P.
[0033] Comparative Example 4 A method for preparing a lightweight and high-strength bulletproof carbon block comprises the following steps: (1) Green petroleum coke with an average particle size of 6 μm was molded on a flat vulcanizer at a pressure of 3 MPa. The block was then kept at an isostatic pressure of 200 MPa for 10 min and left for more than 12 h to obtain a green body.
[0034] (2) The green block obtained in (1) was placed in a pressure sintering furnace. Under 3 MPa argon protection, the temperature was raised to 1050 °C at a rate of 0.2 °C / min and kept at that temperature for 4 h, then the temperature was lowered to below 200 °C at a rate of 0.1 °C / min, and then naturally cooled to room temperature, thereby obtaining the lightweight and high-strength carbon block, named SCB-M6.
[0035] Comparative Example 5 A method for preparing a self-sintered carbon block comprises the following steps: (1) Green petroleum coke with an average particle size of 6 μm was molded on a flat vulcanizer at a pressure of 3 MPa. The block was then kept at an isostatic pressure of 200 MPa for 10 min and left for more than 12 h to obtain a green body.
[0036] (2) The green blocks obtained in (1) are placed in a traditional box-type five-sided furnace sagger, and the remaining space is filled with buried sintering materials. The sintering pressure is close to normal pressure, i.e. 0.1 MPa.
[0037] (3) The sagger prepared in step (2) was placed in a five-sided furnace. Under argon protection, the temperature was raised to 1050 °C at a rate of 0.2 °C / min and kept at that temperature for 4 h. The temperature was then lowered to below 200 °C at a rate of 0.1 °C / min and then naturally cooled to room temperature to obtain the self-sintered carbon block, which was named SCB-K6.
[0038] Comparative Example 6 A method for preparing a lightweight and high-strength bulletproof carbon block comprises the following steps: (1) Green petroleum coke with an average particle size of 13 μm was molded on a flat vulcanizer at a pressure of 3 MPa. The block was then kept at an isostatic pressure of 200 MPa for 10 min and left for more than 12 h to obtain a green body.
[0039] (2) The green block obtained in (1) was placed in a pressure sintering furnace. Under 3 MPa argon protection, the temperature was raised to 1050 °C at a rate of 0.2 °C / min and kept at that temperature for 4 h, then the temperature was lowered to below 200 °C at a rate of 0.1 °C / min, and then naturally cooled to room temperature, thereby obtaining the lightweight and high-strength carbon block, named SCB-M13.
[0040] Comparative Example 7 A method for preparing a self-sintered carbon block comprises the following steps: (1) Green petroleum coke with an average particle size of 13 μm was molded on a flat vulcanizer at a pressure of 3 MPa. The block was then kept at an isostatic pressure of 200 MPa for 10 min and left for more than 12 h to obtain a green body.
[0041] (2) The green blocks obtained in (1) are placed in a traditional box-type five-sided furnace sagger, and the remaining space is filled with buried sintering materials. The sintering pressure is close to normal pressure, i.e. 0.1 MPa.
[0042] (3) The sagger prepared in step (2) was placed in a five-sided furnace, and under argon protection, the temperature was raised to 1050 °C at a rate of 0.2 °C / min and kept at that temperature for 4 h, and then the temperature was lowered to below 200 °C at a rate of 0.1 °C / min, and then naturally cooled to room temperature to obtain the self-sintered carbon block, which was named SCB-K13.
[0043] 1. In the above embodiments, the carbon blocks prepared in Comparative Examples 2 and 3 exhibited obvious cracking, as shown in the optical photographs. Figure 1 As shown, Figure 1 a corresponds to proportion 2, Figure 1 b Corresponding to Example 3, Example 1 successfully produced a carbon block with a complete structure, and the yield rate was 100%. It can be seen that the yield rate of the carbon block is affected by the heating rate and the sintering gas pressure, because rapid heating will aggravate the pyrolysis reaction rate of the raw coke, resulting in too fast release of gas in the block, accumulating gas pressure inside the block, and causing expansion and cracking. At the same time, high sintering gas pressure will accelerate the carbonization of the raw coke and promote the densification of the block, but it may also cause excessive internal stress due to rapid carbonization, increasing the risk of cracks. There is a competitive effect between the heating rate and the sintering gas pressure. The carbonization rate and densification need to be strictly controlled to reduce the risk of expansion and cracking and improve the material yield.
[0044] 2. The basic performance of the carbon blocks prepared in Example 1 and Comparative Examples 1 to 7 were tested. The basic performance parameters of the carbon blocks in Example 1 and Comparative Examples 1 to 7 are shown in Table 1, respectively.
[0045] Table 1. Basic performance parameters of carbon blocks in Example 1 and Comparative Examples 1 to 7 It can be seen from the data in Table 1 that: (1) The present invention uses carbon powder with an average particle size of 2 μm, sintered at a sintering pressure of 3 MPa and a heating rate of 0.2 °C / min, and can obtain a carbon block with good performance and a volume density of up to 1.74 g / cm 3 The open porosity is only 1.2%, and the hardness, flexural strength, compressive strength and toughness can reach 3.23 GPa, 152.35 MPa, 501.72 MPa and 625.63 kJ / m respectively. 3 .
[0046] (2) By comparing Example 1 with Comparative Example 1, Comparative Example 4 with Comparative Example 5, and Comparative Example 6 with Comparative Example 7, it can be seen that pressure sintering can effectively improve the volume density, hardness, flexural strength, compressive strength, toughness and Young's modulus of the carbon block, and reduce the mass loss rate and open porosity of the carbon block. Combined with Comparative Example 3, it can be seen that the sintering pressure is not the higher the better, and the sintering pressure needs to be strictly controlled. At the same time, it can be seen from Example 1, Comparative Example 4 and Comparative Example 6 that as the particle size of the carbon powder increases, the performance parameters of the carbon block, such as the volume density, hardness, flexural strength, compressive strength, toughness and Young's modulus, will decrease, so the average particle size of the carbon powder needs to be controlled.
[0047] 3. Comparison of mechanical properties of carbon blocks obtained in Example 1, Comparative Example 1, and Comparative Examples 4 to 7. Figure 2 As shown in the figure, it can be seen that as the particle size of carbon powder decreases, the strength and toughness of the carbon block are significantly improved. This is because the refined particle size helps to improve the density and uniformity of the material and enhance its anti-destruction ability. Compared with normal pressure sintering (Comparative Example 1, Comparative Example 5 and Comparative Example 7), pressure sintering can further significantly improve the strength and toughness of the carbon block without changing the properties of the raw materials. The synergy of refined particle size and pressure sintering can significantly enhance the ability of the carbon block to resist external damage.
[0048] 4. The comparison results of the nanoindentation load-displacement curves (ac) and hardness (d), Young's modulus (e) and indentation depth (f) of the carbon blocks prepared in Example 1 and Comparative Example 1 and Comparative Examples 4 to 7 are shown in FIG. Figure 3 As shown in the figure, as the particle size of carbon powder decreases, the hardness and Young's modulus of the carbon block increase significantly, while the indentation depth decreases significantly. This shows that refining the particle size effectively improves the density and mechanical properties of the material. In addition, pressure sintering further enhances the hardness and Young's modulus, while significantly reducing the indentation depth. The synergistic effect of the two significantly improves the ability of the carbon block to resist the indentation of hard objects, providing strong support for the preparation of high-strength and high-toughness carbon blocks.
[0049] 5. The SEM images of the carbon blocks obtained in Example 1, Comparative Example 1, and Comparative Examples 4 to 7 are as follows: Figure 4 As shown, Figure 4 (ac) are the surface morphology pictures of the carbon blocks obtained in Example 1, Comparative Example 4 and Comparative Example 6, respectively. Figure 4 (df) are the surface morphology of carbon blocks prepared in Comparative Example 1, Comparative Example 5 and Comparative Example 7 (scale: 100μm). It can be seen from the figure that as the particle size of raw coke decreases, the skeleton structure of the carbon block becomes denser and has fewer pores. Pressure sintering further increases the density of the carbon block and reduces the pores. The dense structure can reduce defects such as microcracks and pores, which is beneficial to the conduction of stress, thereby significantly improving the strength of the carbon block.
[0050] 6. Comparison of the impact resistance of the carbon blocks obtained in Example 1, Comparative Example 1, and Comparative Examples 4 to 7 is shown in the figure below: Figure 5 As shown, Figure 5 a is the impact load-displacement curve of the carbon block. As the coke particle size decreases, the impact load and displacement of the carbon block are greatly increased. Pressure sintering further increases the impact load and displacement of the carbon block ( Figure 5 b). The integral area corresponding to the impact load-displacement curve is the impact energy absorbed by the carbon block, as shown in Figure (5c). The carbon block prepared in Example 1 has a maximum absorption energy of 7.423 J, which is 42.18 times that of the carbon block prepared in Comparative Example 7. Figure 5 d shows the relationship between the average impact load and absorbed energy per gram of the six carbon blocks, and curve fitting is performed. The carbon block prepared in Example 1 can absorb an impact force of 413.37 N and an impact energy of 409.47 mJ per gram, which are 8.81 times and 21.33 times of the carbon block prepared in Comparative Example 7, respectively. This shows that the impact resistance of the carbon block can be greatly improved by increasing the density, strength, hardness and toughness of the carbon block, which lays a foundation for the preparation of the next generation of efficient and lightweight bulletproof materials.
[0051] 7. The fragment reorganization diagram of the carbon blocks prepared in Comparative Example 7 and Example 1 after the impact test is as follows: Figure 6 As shown, 6a and 6c are the upper surface images of the carbon blocks obtained in Comparative Example 7 and Example 1, respectively, 6b and 6d are the bottom images, and the area outside the circle represents the contact area between the carbon block and the impact fixture. It can be seen intuitively that the number of fragments of the carbon block obtained in Comparative Example 1 is significantly less than that in Example 1, which is mainly due to the huge gap in density and mechanical properties between the two. The initiation and expansion of cracks require the absorption of energy, and the conduction of stress requires a medium. Example 1 has a higher density and lower porosity than Comparative Example 7. Therefore, the carbon block obtained in Example 1 can carry a larger load, better stress dispersion, and absorb more energy.
[0052] Finally, it should be noted that the above embodiments of the present invention are only examples for illustrating the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes and modifications can be made based on the above description. It is impossible to list all implementation methods here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. A method for preparing a lightweight and high-strength bulletproof carbon block, characterized in that: The carbon powder with a D50 of 0.1-5 μm is pressed into a green body, and then the green body is placed in a pressure sintering furnace and calcined at 1-5 MPa to obtain the lightweight and high-strength bulletproof carbon block.
2. The method for preparing a lightweight and high-strength bulletproof carbon block according to claim 1, characterized in that: The carbon powder is one or more of granulated powder, raw pitch coke, raw petroleum coke and mesophase carbon microspheres.
3. The method for preparing a lightweight and high-strength bulletproof carbon block according to claim 1, characterized in that: The specific steps of compression molding are: first, pre-molding is performed on a flat vulcanizer at a pressure of 1-15 MPa for 10-30 seconds, and then the green body is obtained by holding the pressure at 150-250 MPa for 10-20 minutes on a cooling press, and then the green body is left for more than 12 hours.
4. The method for preparing a lightweight and high-strength bulletproof carbon block according to claim 1, characterized in that: During calcination, under the protection of inert gas, the temperature is raised to 800~1200℃ at a rate of 0.1~0.3℃ / min and kept at that temperature for 2~6 hours, and then cooled to room temperature.
5. The method for preparing a lightweight and high-strength bulletproof carbon block according to claim 4, characterized in that: The heating rate is 0.2 °C / min.
6. A method for preparing a lightweight and high-strength bulletproof carbon block according to claim 1 or 5, characterized in that: During sintering, the pressure in the pressurized sintering furnace is 3MPa.
7. A lightweight and high-strength bulletproof carbon block, characterized in that: The carbon block is prepared by the method for preparing a lightweight and high-strength bulletproof carbon block as described in any one of claims 1 to 6.